Microbial metabolites and immune modulation - Hassan Ghasemi (Journal of Preventive and Complementary Medicine)
The human microbiota, a complex ecosystem of microorganisms, has garnered significant attention for its profound influence on host health. Beyond their structural roles, these microbes produce a diverse array of bioactive metabolites that interact with the host immune system. Microbial metabolites serve as molecular mediators, orchestrating immune homeostasis and modulating responses to pathogens, inflammation, and diseases.1,2 Understanding these interactions has opened new avenues for therapeutic interventions targeting immune-related disorders. This review explores key microbial metabolites and their roles in immune modulation, focusing on short-chain fatty acids (SCFAs), secondary bile acids, tryptophan metabolites, and other emerging bioactives.2 Microbial metabolites include short-chain fatty acids such as acetate, propionate, and butyrate, which are products of dietary fiber fermentation by gut microbiota. These metabolites play a crucial role in regulating immune homeostasis. Acetate can be absorbed systemically, contributing to energy metabolism and indirectly modulating immune responses. Butyrate is particularly significant due to its ability to influence T-cell differentiation, promoting the expansion of regulatory T cells (Tregs) that dampen inflammatory processes while simultaneously suppressing pro-inflammatory Th17 responses. Propionate, another SCFA, has been linked to the inhibition of histone deacetylases, which are involved in gene regulation, further supporting anti-inflammatory pathways.3,4 These metabolites also modulate macrophage function by promoting a shift toward an anti-inflammatory M2 phenotype, a process essential for resolving inflammation and facilitating tissue repair.5 Additionally, they enhance gut barrier integrity by upregulating proteins involved in epithelial tight junctions, reducing the translocation of harmful microbial components into systemic circulation and thereby mitigating systemic inflammation.6 Secondary bile acids, produced through the microbial biotransformation of primary bile acids synthesized in the liver, exhibit immunomodulatory properties. They interact with specific immune receptors such as G-protein-coupled bile acid receptor 1 (TGR5) and farnesoid X receptor (FXR). These interactions regulate inflammation by modulating the production of pro-inflammatory cytokines and altering dendritic cell activity, which is critical for antigen presentation and immune tolerance.7 The microbial metabolism of tryptophan, an essential amino acid derived from dietary proteins, results in the production of indole derivatives that activate the aryl hydrocarbon receptor (AhR). This receptor is pivotal in maintaining intestinal homeostasis, regulating barrier function, and promoting mucosal immunity. Activation of AhR enhances the production of IL-22, a cytokine essential for strengthening epithelial defenses against pathogenic invasion and ensuring microbiota-immune equilibrium.8 Emerging bioactive compounds such as polysaccharide A (PSA) from Bacteroides fragilis modulate dendritic cells, inducing Tregs that contribute to immune tolerance. Even lipopolysaccharides (LPS), traditionally regarded as pro-inflammatory, can have nuanced roles; at low doses, they may condition immune cells to adopt a tolerogenic state, highlighting the complexity of microbial metabolite interactions.9 Microbial metabolites significantly influence innate immunity by enhancing the pathogen-clearing abilities of macrophages, as SCFAs optimize their phagocytic functions. Indole derivatives regulate natural killer (NK) cell activity, fine-tuning their cytotoxic responses and cytokine secretion to ensure the precise elimination of infected or malignant cells. Secondary bile acids suppress the NLRP3 inflammasome, a multiprotein complex implicated in chronic inflammatory disorders, thereby reducing harmful inflammatory cascades.10 Adaptive immunity is also intricately modulated by microbial metabolites. For instance, butyrate epigenetically alters regulatory T cells (Tregs) by promoting histone acetylation, significantly enhancing their suppressive capacity and maintaining immune tolerance. SCFAs further boost immunoglobulin A (IgA) secretion, a critical component of mucosal immunity that fortifies the first line of defense against pathogens. Indole derivatives help shift the Th1/Th2 balance toward equilibrium, mitigating the risk of autoimmunity while ensuring effective immune responses.11 Therapeutically, microbial metabolites offer promising interventions for various immune-related diseases. In autoimmune conditions such as inflammatory bowel disease (IBD), SCFAs restore epithelial integrity and dampen inflammation by modulating local immune responses within the gut. AhR agonists derived from tryptophan metabolism enhance mucosal barrier functions, reducing disease severity. In rheumatoid arthritis, butyrate suppresses Th17-mediated joint inflammation, highlighting its systemic immunomodulatory capabilities. In cancer immunotherapy, SCFAs enhance the efficacy of immune checkpoint inhibitors like anti-PD-1/PD-L1 therapies by reshaping the tumor microenvironment toward an anti-tumoral state. Indole derivatives exhibit anti-inflammatory properties that suppress tumor-promoting inflammation, thereby supporting the host’s anti-cancer immunity.12 In infectious diseases, microbial metabolites enhance pathogen clearance by activating macrophages and NK cells. SCFAs, along with PSA, have shown promise as vaccine adjuvants by boosting antigen-specific immune responses and enhancing both the magnitude and quality of protective immunity. These findings underscore the potential of leveraging microbial metabolites to improve vaccine efficacy, particularly in immunocompromised populations or during outbreaks of novel pathogens.13 However, challenges in this field persist. Inter-individual variability in microbiota composition and function leads to significant differences in metabolite production and immune outcomes, necessitating personalized approaches to therapeutic applications. Further research is needed to dissect the precise molecular pathways linking specific metabolites to immune responses, as much remains unknown about their multifaceted roles. Additionally, translational hurdles -such as ensuring the stability, bioavailability, and targeted delivery of microbial metabolites- must be overcome to realize their full clinical potential.14 Microbial metabolites are central to immune modulation, bridging the intricate relationship between host and microbiota. Their therapeutic potential spans autoimmune disorders, cancer, and infectious diseases, offering innovative solutions for immune-related challenges. Continued exploration of these bioactive molecules, supported by advances in microbiome research and systems biology, will illuminate new pathways for treatment and enhance our understanding of host-microbiota interactions.14